Digital Literacy Assisted by E-Litera Media Nonfiction Text Materials to Increase Interest in Learning - Kardiana Metha Rozhana; Kardiana Zendha Avalentina; Adi Tri Atmaja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The objective of this research is to improve student learning interest in nonfiction texts through the implementation of E-Litera, a digital-based interactive literacy media. This study utilized a classroom action research design conducted in two cycles involving 24 fourth-grade students at SDN Sidomulyo. Data were obtained from questionnaires, observations, interviews, and documentation. The results showed a significant improvement in student learning outcomes throughout the research process. In the pre-action phase, only 8 students (33.3%) achieved the minimum mastery criteria, while 16 students (66.7%) did not meet the criteria. This figure increased to 12 students (50%) in the first cycle, and significantly rose to 20 students (83.3%) in the second cycle. The enhanced performance in the final cycle reflects the effectiveness of E-Litera in providing visually engaging and structured content, which helped deepen students' understanding of nonfiction materials. These findings support the use of E-Litera as a meaningful and engaging digital media to foster reading interest and improve comprehension skills in elementary education. By using E-Litera, the teaching and learning process can be more effective and enjoyable, ultimately improving the quality of student learning.